2002
DOI: 10.1093/njaf/19.3.106
|View full text |Cite
|
Sign up to set email alerts
|

Forest Productivity and Commercial Value of Pre-Law Reclaimed Mined Land in the Eastern United States

Abstract: The purpose of this study was to investigate the effects of mining practices used prior to the passage of the 1977 Surface Mining Control and Reclamation Act (SMCRA) on forest productivity and commercial value of reclaimed forest sites. Forest productivity and value of 14 mined and 8 nonmined sites throughout the eastern and midwestern coalfield regions were compared. Forest productivity of pre-SMCRA mined sites was equal to or greater than that of nonmined forests, ranging between 3.3 m3ha-1yr-1 and 12.1 m3ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…The ecosystem, according to the traditional definition (Golley 1993), should consist of an integrated system of biotic and abiotic elements where all the trophic layers contain a complete set of species ensuring the circulation of matter and energy flow. A complete assessment of the reclamation and afforestation processes should take into consideration many ecological factors (Rodrigue et al 2002). Of particular importance is the need to understand soils processes, element flux (Bradshaw 1983; Daniels et al 1992; Li and Daniels 1994; Bendtfeldt et al 2001; Schaaf 2001; Knoche et al 2002; Pietrzykowski 2010a) and energy balance (Pietrzykowski and Krzaklewski 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The ecosystem, according to the traditional definition (Golley 1993), should consist of an integrated system of biotic and abiotic elements where all the trophic layers contain a complete set of species ensuring the circulation of matter and energy flow. A complete assessment of the reclamation and afforestation processes should take into consideration many ecological factors (Rodrigue et al 2002). Of particular importance is the need to understand soils processes, element flux (Bradshaw 1983; Daniels et al 1992; Li and Daniels 1994; Bendtfeldt et al 2001; Schaaf 2001; Knoche et al 2002; Pietrzykowski 2010a) and energy balance (Pietrzykowski and Krzaklewski 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There are few peer‐reviewed reports of forest growth on reclaimed mine sites in the Central Appalachians, and their conclusions are divergent. Several studies 49,50 have reported limited woody tree recruitment and growth in a series of MTVF sites reclaimed under the SMCRA, while Rodrigue et al 51 and Amichev et al 52 estimated similar levels of forest productivity between 14 surface mine sites reclaimed prior to the 1977 enactment of the SMCRA and adjacent unmined stands. Revegetation is required under the SMCRA, but this has typically involved hydroseeding the recontoured landscape with a mixture of grasses 44 so that forest regrowth depends upon dispersal and recruitment.…”
mentioning
confidence: 99%
“…The grand total C accumulations in the form of biomass, litter layer, and soil organic matter (SOM) (Rodrigue 2001, Rodrigue et al 2002, as well as the prolonged C storage time, such as standing timber and long-term forest products (IPCC 2003, Skog and Nicholson 1998, Spinney et al 2005, greatly increase the function of forests in reducing atmospheric CO 2 . In his summary of the global carbon cycle, Schlesinger (1995) suggests that the potential for enhanced carbon sequestration in terrestrial ecosystems is much greater in forest vegetation than in soils, which makes reforestation and forest fertilization attractive short-term practices for atmospheric CO 2 sequestration on land.…”
Section: Methodsmentioning
confidence: 99%
“…While improved forest management practices may lead to an increase of the forest productivity (Rodrigue et al 2002) and the carbon sequestration potential of reclaimed forest lands in the Appalachian and Midwestern coalfields of the United States (Amichev et al 2004), there are several challenges associated with verifying C stock changes, especially in the soil component of these forest ecosystems. Many soil factors have an effect on SOM accumulation and decomposition in mine soils, including the methods of mine spoil placement and site reclamation after coal mining and the subsequent development of mine soils largely influenced by the vegetation they support and weathering processes (Chichester and Hauser 1991).…”
Section: Methodsmentioning
confidence: 99%